Chinese Music Teachers’ Perceptions of Context Issues and Transmission Modes in World Music Teaching - Zhuang, Chun Mei; Pan, Kok Chang (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Based on his academic background in multicultural music education and ethnomusicology, Huib Schippers developed the Seven-Continuum Transmission Model (SCTM) in 2004 to describe the teaching situations of world music. The current study adopted the SCTM as a framework to investigate Chinese music teachers’ perceptions of context issues (tradition, authenticity, and context) and transmission modes (analytic/holistic, notation based/aural, and tangible/intangible) in world music teaching. Semi-structured in-depth interviews were conducted using a qualitative methodology with nine primary and secondary school music teachers from different provinces in China. This study found that Chinese music teachers’ perceptions of context issues and transmission modes in world music teaching were more inclined to the formal, institutional settings rather than the informal, often community-based process. In addition, the music teachers were also influenced more by the “Eurocentrism” values; however, their perceptions were less affected by ethnomusicology that interprets human music from a cultural perspective and by multicultural music education.